Fatal Asphyxiation in Bottlenose Dolphins (Tursiops truncatus) from the Indian River Lagoon - Stolen, Megan; St. Leger, Judy; Durden, Wendy Noke; Mazza, Teresa; Nilson, Erika (PLOS ONE, 2013)
Multiple single case reports of asphyxiation in dolphins caused by fish lodged in the esophagus exist. However, the significance of this cause of mortality in a single population has not been documented. We performed a retrospective evaluation of pathology records from stranded bottlenose dolphins (Tursiops truncatus) from the Indian River Lagoon to evaluate the impact of this cause of death on this population. From 1997 to 2011, asphyxiation due to choking was identified as the cause of death in 14 of 350 cases (4%). Sampling of an unrelated but adjacent population over this same period yielded 186 necropsy cases of bottlenose dolphins with no cases of asphyxiation. Asphyxiated animals presented with a fish lodged in the cranial esophagus associated with a dislocated and obstructed or compressed larynx. There was no clear sex predilection. Affected animals included 12 adults and two juveniles. The fish species involved included sheepshead, black chin tilapia and striped mojarra. In five cases, recreational fishing gear was also present. Cetacean choking is related to selection of prey fish species with strong dorsal spines and may be secondarily associated with fish attached to fishing gear. Prey abundance and dolphin behavior may influence these selections. Environmental alterations leading to changes in prey availability or increased interactions with fishing gear may change the significance of fatal choking in dolphin populations.